Studi komparasi antara model pembelajaran think talk write dan model pembelajaran direct instruction terhadap keterampilan menulis teks eksplanasi ditinjau dari motivasi belajar pada peserta didik kelas V sekolah dasar - Dwi Agus Ariyanto; Slamet Slamet; Tri Budiharto (Universitas Sebelas Maret, 2019)
Abstract: The purposes of this research is to find out of (1) the differences in explanation text writing skill between students that learned by Think Talk Write learning models and Direct Instruction learning models (2) knowing the differences in students who have high and low learning motivation towards explanation text writing skill (3) the effect interaction of leraning-models and leraning motivation toward explanation text writing skill. The population of the research was all of students grade V SD N in Laweyan District Surakarta City. Grade V SD N Tegalsari and grade V SD N Bumi 1 were selected as the sample through cluster random sampling. This research use experimental method with 2x2 factorial design. Data were collected by means of questionnaire for students learning motivation data and test for the data of students explanation text writing skill. Those data were analyzed with two-way Anava test with different content of cell with level of significance 0,05. The result showed that, (1) there were differences in explanation text writing skill between students who taught by Think Talk Write and Direct Instruction learning model (FA = 4,15 > Ftabel = 4,00) (2) there were difference in explanation text writing skill between students who have high motivation and low motivation (FB = 4,05 > Ftabel = 4,00) (3) there was no effect interaction between the learning-model and learning-motivation toward explanation text writing skill (FAB = 0,41 < Ftabel = 4,00).Keywords : Think Talk Write, Direct Instruction, explanation text writing skill, elementary school